Dental treatment for children under general anesthesia - Miyazawa, H; Namba, H; Seiki, K; Karasawa, S; Kaneko, H; Imanishi, T; Takeuchi, T; Hayashi, N; Hirose, I (Shoni shikagaku zasshi = the Japanese journal of pedodontics, 1990)
A clinico-statistical survey was carried out on dental treatment for children under general anesthesia who visited the clinic of Pedodontic Department, Matsumoto Dental College Hospital during the period of 1986 to 1989. The number of cases subjected in this survey was 108 (57 boys 51 girls), aged from one year and 5 months to 8 years and 9 months. All of these patients were admitted to the hospital for 3 days and were treated under general anesthesia, using GOE in 107 cases (in 80 cases by nasal intubation, in 27 cases by oral intubation). One case was administrated by intravenous anesthesia with Ketamine. The results were as follows: 1. The patient ages of the patients ranged from one year 5 months to 8 years 9 months. 2. Thirteen percent of the patients were handicapped. Fifty three percent of the patients had to visit hospitals in remote areas. 3. The number of restored teeth per patient was 15 on the average. The teeth were treated with composite resin filling in 8.5 teeth, composite resin crown in 2.6 teeth, metal crown 3.6 teeth and other material in 0.8 (extraction). 4. Pulpal treatment was carried out on 42 percent of the subjected teeth. 5. The average anesthesia administration time was 3 hours and 28 minutes. No serious trouble was observed although minor complications were seen post-operatively such as high fever or vomiting in some cases.